A cross-disciplinary overview of naturally derived materials for electrochemical energy storage. (March 2018) - Gao, Mengyao; Pan, Shu-Yuan; Chen, Wen-Chang; Chiang, Pen-Chi
Abstract: Due to global climate change and resource shortages, significant attention has been focused on exploiting environmentally friendly materials, such as naturally derived materials (e.g., biomass), for electrochemical energy storage to achieve a circular economy. One current area of research focus is bionics, which is a promising strategy to make materials with three-dimensional ordered structures that offer multiple contributions to bulk electrochemical properties. To develop high-performance energy storage devices, this article first reviews advances in the design and synthesis of nanostructured materials from plant-based biomass. The challenges and limitations on achieving high-performance rechargeable batteries are also illustrated and discussed from the materials design point of view. Then, from the perspective of chemical engineering, the performance of porous carbon from plant-based biomass for various applications is elucidated. Comprehensive performance evaluations on the relationship between the structure and electrochemical properties of biomass-derived materials are performed and summarized. Finally, the environmental benefits and impacts of electrochemical energy storage devices using biomass are discussed. From the perspective of environmental engineering, the recycling and reuse of metal components from spent batteries through the concept of green chemistry are presented. This article should be considered a pioneering review providing a holistic overview of electrochemical energy storage devices using plant-based biomass from a cross-disciplinary perspective that encompasses on materials science, chemical engineering and environmental engineering. Graphical abstract: Highlights: Challenges and opportunities of plant-based biomass for EES devices are provided. Advances in design and synthesis of nanostructure plant-based carbons are reviewed. Performance of plant-based porous carbon for EES devices (e.g., LIB) is elucidated. Relationship between the structure and electrochemical properties is summarized. Environmental benefits and impacts of EES devices using biomass are discussed.